2015
DOI: 10.1016/j.combustflame.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanostructure, oxidative pressure and extent of oxidation on model carbon reactivity

Abstract: Oxidation kinetics and fringe analysis studies of three "model" carbons, ranging from fullerenic to onion-like nanostructures and a reference diesel soot were performed in a thermogravimetric analyzer. The samples were oxidized isothermally at temperatures ranging from 575 to 775 °C in air. Multiple tests were performed to obtain the most favorable operating conditions to minimize mass-transfer diffusion limitations in the experiments. First-order reaction kinetics and an Arrhenius-type equation were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 44 publications
(55 reference statements)
7
53
1
Order By: Relevance
“…A study by Wu et al [59] on GDI soot showed that the fringe length also varied with the air-fuel-ratio of the engine, from 0.83 nm to 0.91 nm. For soot obtained from diesel engines, Jaramillo et al [41] and Sakai et al [42] reported similar fringe lengths of 0.98 nm and 1 nm respectively. However, in studies by Li et al [9] and Xu et al [60] the fringe length of diesel soot was observed to be affected by fuel injection splitting (1.16e1.2 nm) and injection timing (1.12e1.4 nm), respectively.…”
Section: Fringe Analysismentioning
confidence: 65%
See 4 more Smart Citations
“…A study by Wu et al [59] on GDI soot showed that the fringe length also varied with the air-fuel-ratio of the engine, from 0.83 nm to 0.91 nm. For soot obtained from diesel engines, Jaramillo et al [41] and Sakai et al [42] reported similar fringe lengths of 0.98 nm and 1 nm respectively. However, in studies by Li et al [9] and Xu et al [60] the fringe length of diesel soot was observed to be affected by fuel injection splitting (1.16e1.2 nm) and injection timing (1.12e1.4 nm), respectively.…”
Section: Fringe Analysismentioning
confidence: 65%
“…Thus, the soot-in-oil would be less oxidised than soot from the exhaust gas due to a shorter residence time in the combustion chamber. Jaramillo et al [41] found a linear decrease of the fringe length with increasing degree of oxidation of diesel soot. Similarly, Rohani and Bae [61] observed lower fringe length and higher tortuosity for soot obtained directly from the in-cylinder spray than for particles from the exhaust gas.…”
Section: Fringe Analysismentioning
confidence: 99%
See 3 more Smart Citations